Extract of seaweed Gracilaria verrucosa as immunostimulant to controlling white spot disease in Pacific white shrimp Litopenaeus vannamei - Zahra, Aminatul; Sukenda, Sukenda; Wahjuningrum, Dinamella (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT This experiment was conducted to examine effect of Gracilaria verrucosa extract in diet with different dosages to enhance immune response and resistance against white spot syndrome virus (WSSV) in the Pacific white shrimp. The experiment consisted of six treatments in three replicates respectively, namely K- (without extract), K + (without extract + infected WSSV), A (2 g/kg of feed + infected WSSV), B (3 g/kg of feed + infected WSSV), C (4 g/kg of feed + infected WSSV), and D (5 g/kg of feed + infected WSSV). White shrimp with initial body weight of 6.07±0.10 g were reared in the (60×30×30) cm with density of 10 shrimps/aquarium. G. verrucosa was extracted with ethyl acetate. Pacific white shrimp had been fed medicated feed three times daily 3% at satiation for 14 days. At 15th days, white shrimp were challenged with WSSV at 0.1 mL/shrimp intramuscularly. The results showed that the immune response shrimp (total hemocyte count, phagocytic activity, respiratory burst, and phenoloxidase activity) fed medicated feed increased significantly compared to positive and negative controls. The best relative percent survival post-challenge test was at 4 g/kg dose of G. verrucosa, i.e 41.07±3.09%. Confirmation of WSSV using PCR showed that shrimps (A, B, C, D, and K+) were positively infected by WSSV. It was concluded that 4 g/kg dose of G. verrucosa gave the best result to enhance immune response and resistance to WSSV infection. Keywords: seaweed, Gracilaria verrucosa, immunostimulant, Pacific white shrimp, WSSV ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh pemberian ekstrak Gracilaria verrucosa melalui pakan dengan dosis yang berbeda untuk meningkatkan imunitas dan resistensi udang vaname terhadap serangan white spot syndrome virus (WSSV). Penelitian ini terdiri atas enam perlakuan dan masing-masing tiga ulangan, yaitu K- (tanpa ekstrak), K+ (tanpa ekstrak + infeksi WSSV), A (2 g/kg pakan + infeksi WSSV), B (3 g/kg pakan + infeksi WSSV), C (4 g/kg pakan + infeksi WSSV), dan D (5 g/kg pakan + infeksi WSSV). Udang vaname dengan bobot 6,07±0,10 g dipelihara dalam akuarium dengan ukuran (60×30×30) cm dengan padat tebar 10 ekor/akuarium. Udang diberi pakan perlakuan secara at satiation sebanyak tiga kali sehari selama 14 hari. Pada hari ke-15 diuji tantang dengan WSSV pada dosis 0,1 mL/ekor secara intramuskular. Hasil penelitian menunjukkan bahwa respons imun udang (total hemosit, aktivitas fagositik, respiratory burst, dan aktivitas fenoloksidase) yang diberi pakan mengandung ekstrak G. verrucosa mengalami peningkatan signifikan dibanding perlakuan kontrol positif maupun negatif. Relative percent survival terbaik pasca uji tantang pada perlakuan C (4 g/kg), yaitu 41,07±3,09%. Konfirmasi WSSV dengan menggunakan PCR menunjukkan hasil bahwa udang (A, B, C, D, and K+) positif terinfeksi WSSV. Disimpulkan bahwa dosis ekstrak G. verrucosa 4 g/kg pakan memberikan hasil terbaik untuk meningkatkan respons imun pada udang vaname  dan resistensi terhadap WSSV.   Kata kunci: rumput laut, Gracilaria verrucosa, imunostimulan, udang vaname, WSSV